Characterization of the exploring agricultural properties of beef cattle production - Bezerra, Leilson Rocha; de Araújo, Marcos Jácome; Marques, Carlo Aldrovandi Torreão; Torreão, Jacira Neves da Costa; Vaz, Raimundo Rosal; Oliveira Neto, Cezario Batista de (Comunicata Scientiae, 2013)
This research aimed to identify and to characterize the profile of the exploring agricultural properties of beef cattle production in the micro region of Alto Médio Gurguéia. The small producer characterization based on the scientific knowledge on the local agricultural reality is essential to develop policies for the dissemination of technologies, programs and projects for agricultural development. This way, a semi-structured questionnaire was elaborated using questions about general issues of farm profile and creation system adopted by producers, issues related to producers’ social aspects, livestock zootechnical conditions and technical and marketing conditions of meat production. This questionnaire was applied to 104 producers in the municipality in an eclectic and comprehensive way in order to obtain a sample as representative as possible. The data collection period was between September, 2008 and December, 2009. Themajority of producers keep a typical family farming profile, with emphasis on subsistence activity, low technological level and little knowledge. Turning them less competitive and more susceptible to climatological, management or marketing adversities.